Hierarchically Designed Light Trapping Films for All‐Day Operating Semitransparent Photovoltaics. Issue 41 (27th September 2020) - Lee, Junghwa; Moon, Yoon‐Jong; Cho, Junhee; Park, Sangpil; Baek, Seunghun; Nam, Minwoo; Kim, Sun‐Kyung; Ko, Doo‐Hyun
Abstract: Highly efficient light‐trapping polymer films are designed to enhance the photocurrent of semitransparent organic photovoltaics (ST‐OPVs) in indoor and outdoor conditions. An asymmetric‐reflection film fabricated through the novel combination of randomly arranged nanostructures with periodically assembled microstructures exhibits selectivity for the direction of incident light. The film effectively traps light within the device by selectively reflecting light that escapes from the inside out. Moreover, this light‐trapping effect is maximized by attaching the films to both sides of the bifacial ST‐OPVs operating under solar and indoor sources, simultaneously. Accordingly, the light‐trapping polymer film platform presents short‐circuit current density (   J SC ) enhancement of ST‐OPVs by 13.49% and 46.19% under air mass 1.5G and light‐emitting diodes (1000 lux) illumination, respectively, and provides new opportunities for ST‐OPVs in a variety of practical applications. Abstract : The reported hierarchically designed light‐trapping system effectively confines light inside bifacially operating semitransparent photovoltaics. The trapping system consists of two asymmetric‐reflection surfaces, which exclusively permit the one‐way transmission of the incident light. All‐day operating semitransparent photovoltaics developed herein simultaneously exhibit the properties of a nearly black absorber and high‐performance current generation under solar and artificial light illumination.